Molecular cloning, functional expression, and pharmacological characterization of an N-methyl-D-aspartate receptor subunit from human brain. - Planells-Cases, R (1993)
A cDNA encoding a full-length N-methyl-D-aspartate (NMDA) receptor subunit 1, hNR1, was isolated from a human brain cDNA library. The hNR1 cDNA encodes an open reading frame of approximately 2.7 kb that shares high homology with the rat brain NMDA receptor subunit 1 and the mouse zeta 1 subunit. The hNR1 sequence, however, diverges from the rodent and murine homologs near the C terminus, suggesting that they represent alternatively spliced messages of the same gene. Oocytes injected with cRNA synthesized from the hNR1 cDNA express glutamate and NMDA-activated currents in the presence of glycine. Currents are blocked by the NMDA-receptor-specific antagonists 2-amino-5-phosphovaleric acid and 7-chlorokynurenate, and the open channel blockers MK-801 and phencyclidine, by Mg2+ ions in a voltage-dependent manner, and by Zn2+. Expressed hNR1 homomeric receptor channels exhibit the high Ca2+ permeability characteristic of neuronal NMDA receptors. Therefore, the cDNA clone hNR1 codes for a human brain NMDA receptor subunit cognate to the rodent and murine brain NR1 subunits.